2020
DOI: 10.1002/jso.26138
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of lymph node examination in patients undergoing curative‐intent resection for adrenocortical carcinoma

Abstract: Background: Adrenocortical carcinoma (ACC) is a rare tumor and the role of lymph node dissection remains ill-defined. This study evaluates the effect of no dal examination on prognosis and survival in patients undergoing curative-intent resection of ACC. Methods: The National Cancer Database (2004-2015) was queried for patients undergoing margin-negative resection for ACC. Patients with distant metastases, neoadjuvant therapy, multivisceral resection and T4 tumors were excluded. Results: Among 897 patients, 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Lymph node metastasis is associated with advanced tumors ( p = 0.4). Median overall survival was incrementally worse with increasing number of positive lymph nodes (88.2 months for N0, 34.9 months for 1–3 positive nodes, and 15.6 months for ≥4 positive nodes, p < 0.001) [ 67 ]. The optimal extent of lymphadenectomy in ACC is still not known.…”
Section: Resultsmentioning
confidence: 99%
“…Lymph node metastasis is associated with advanced tumors ( p = 0.4). Median overall survival was incrementally worse with increasing number of positive lymph nodes (88.2 months for N0, 34.9 months for 1–3 positive nodes, and 15.6 months for ≥4 positive nodes, p < 0.001) [ 67 ]. The optimal extent of lymphadenectomy in ACC is still not known.…”
Section: Resultsmentioning
confidence: 99%
“… 107 The authors found that lymphadenectomy was associated with a significantly higher 5-year OS rate of 76% compared to 59% in the group that had no lymph nodes excised. 107 However, multiple studies using the SEER registry and National Cancer Database (NCDB) have shown contradictory results, with either no effect, 108 worse survival, 109 112 or a marginal improvement in survival, 113 in patients who underwent lymphadenectomy. Reasons for these discrepancies include the fact that the inclusion criteria in these studies differ widely by stage, presence of metastases, multivisceral resection, and margin status.…”
Section: Treatmentmentioning
confidence: 99%
“…Of these, 14 studies were excluded due to missing data pertaining to our predefined endpoints. Eleven studies were included in the qualitative analysis [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. These studies reported patients from five different cancer databases, and study characteristics are summarized in Table A2 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported the postoperative mortality for the LND and NoLND group [ 17 , 19 , 20 ]. These studies used different time points as the cut-off for mortality, which makes a direct comparison difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation